Transient Increase of Retinal Nerve Fiber Layer Thickness after Vitrectomy with ILM Peeling for Idiopathic Macular Hole - Ohta, Kouichi (J Ophthalmol, 2016)
Purpose. The purpose of this study was to determine the long-term changes in the circumpapillary retinal nerve fiber layer (RNFL) thickness following macular hole surgery with internal limiting membrane (ILM) peeling combined with phacoemulsification. Methods. Thirty-eight eyes of 37 patients who had pars plana vitrectomy (n = 36) between 2010 and 2014 were studied. The average thicknesses of the global and the six sectors of the RNFL were determined before and at 1, 3, 6, 12, and 24 (n = 22) months (M) after the surgery by spectral-domain optical coherent tomography. The postoperative mean RNFL thickness at each time was compared to that before the surgery by paired t-tests. Results. The RNFL of the operated eyes was significantly thicker at 1 month (1 M) and 3 M in all but the inferior-nasal sectors. The significant increase remained until 12 M in the superior-temporal and superior-nasal sectors. In addition, the RNFL was also significantly thicker in the temporal-inferior sector at 12 M based on the findings in 38 eyes. Conclusions. The postoperative RNFL was thicker in all but the nasal-inferior sector for at least 12 M after surgery. This prolonged increase of the RNFL thickness may indicate damage and mild edema of the RNFL.